Light Suppresses Bacterial Population through the Accumulation of Hydrogen Peroxide in Tobacco Leaves Infected with Pseudomonas syringae pv. tabaci - Cheng, Dan-Dan; Liu, Mei-Jun; Sun, Xing-Bin; Zhao, Min; Chow, Wah S.; Sun, Guang-Yu; Zhang, Zi-Shan; Hu, Yan-Bo (Frontiers in Plant Science, 2016)
Pseudomonas syringae pv. tabaci (Pst) is a hemibiotrophic bacterial pathogen responsible for tobacco wildfire disease. Although considerable research has been conducted on the tobacco plant’s tolerance to Pst, the role of light in the responses of the photosystems to Pst infection is poorly understood. This study aimed to elucidate the underlying mechanisms of the reduced photosystem damage in tobacco leaves due to Pst infection under light conditions. Compared to dark conditions, Pst infection under light conditions resulted in less chlorophyll degradation and a smaller decline in photosynthetic function. Although the maximal quantum yield of photosystem II (PSII) and the activity of the photosystem I (PSI) complex decreased as Pst infection progressed, damage to PSI and PSII after infection was reduced under light conditions compared to dark conditions. Pst was 17-fold more abundant in tobacco leaves under dark compared to light conditions at 3 days post-inoculation (dpi). Additionally, hydrogen peroxide (H2O2) accumulated to a high level in tobacco leaves after Pst infection under light conditions; although to a lesser extent, H2O2 accumulation was also significant under dark conditions. Pretreatment with H2O2 alleviated chlorotic lesions and decreased Pst abundance in tobacco leaves at 3 dpi under dark conditions. Methyl viologen (MV) pretreatment had the same effects under light conditions, whereas 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) pretreatment aggravated chlorotic lesions and increased the Pst population. These results indicate that chlorotic symptoms and the size of the bacterial population are each negatively correlated with H2O2 accumulation. In other words, light appears to suppress the Pst population in tobacco leaves through the accumulation of H2O2 during infection.